Persistent Creativity Making the Case for Art, Culture and the Creative Industries - Campbell, Peter (Sociology of the Arts, 2019)
"Campbell offers a forensic critique of the rise of creativity as central to economic and urban policy discourses in the UK over recent decades. Persistent Creativity is essential reading for anyone interested in the past and the future of the arts, culture and creativity, and how these can be used as the basis of urban policy." - Susan Luckman, School of Creative Industries, University of South Australia, Australia "In this punctiliously researched and incisive narrative, Campbell delves into the depths of the 'Creativity Agenda'. Taking to task a variety of policy documents, statistics and literature, Persistent Creativity offers a unique contribution, questioning 'what exactly is meant by the term creativity?'" - Oli Mould, Royal Holloway, University of London, UK "Campbell's book offers a lucid and balanced account of creative industries policy, fundamental to scholars and policymakers alike." -Kate Oakley, University of Glasgow, UK Recent years have seen the increasing valuation and promotion of 'creativity'. Future success, we are often assured, will rest on the creativity of our endeavours, often aligned specifically with 'cultural' activity. This book considers the emergence and persistence of this pattern, particularly with regards to cultural policy, and examines the methods and evidence deployed to make the case for art, culture and the creative industries. The origins of current practices are considered, as is the gradual accretion of a broad range of meanings around the term 'creative', and the implications this has for the success of the wider 'Creativity Agenda'. The specific experience of the city of Liverpool in adopting and furthering this agenda both in the UK and beyond is considered, as is the persistence of a range of problematic, and often contradictory, assumptions and practices relating to this agenda up to the present day.